INFORMATION SUPPORT AND TRENDS IN THE DEVELOPMENT OF GRANT ACTIVITY IN HIGHER EDUCATION INSTITUTIONS - Trokhanovskyі , V. D.; Vasyliuk , M. M. (The actual problems of regional economy development, 2024)
The article examines the information support and trends in the development of grant activities in higher education institutions, the improvement of grant activities in higher education institutions in order to respond to current challenges and opportunities, as well as to increase the efficiency and accessibility of this tool for the academic community. This study aims to thoroughly analyze current trends in the grantmaking activities of Ukrainian higher education institutions (HEIs), identify important challenges and prospects for the development of this area. The main goal is to develop recommendations for optimizing the processes of attracting grant funds and supporting research and educational initiatives. The study used a variety of methods, such as analysis of scientific publications, study of statistical data, expert evaluation and comparative analysis of granting practices. The main trends in the grant sector were analyzed, and the level of accessibility and quality of information on grant opportunities for higher education institutions was assessed. The article reveals an increase in competition for grants, the active use of interdisciplinary projects, and the importance of digital technologies in grantmaking. The study also noted a trend toward greater international cooperation and the development of objective performance evaluation systems. In the context of the Ukrainian war, it is especially important to develop international cooperation and effectively use grant resources to support research and educational initiatives. Special attention is paid to improving the efficiency and accessibility of grant opportunities for the academic community. This is important given the growing competition for grants, the trend toward interdisciplinarity, and the need for global cooperation. The results of the analysis can be an important source of information for the management of higher education institutions and research groups in improving their grantmaking strategies and ensuring further scientific development. This study emphasizes the key role of grantmaking in Ukrainian higher education institutions for scientific and educational development. It identifies strategies for optimizing this process in the face of current challenges and contributes to the achievement of global sustainable development goals.